Italianity and Polonity in the concept of civil society - Kozakiewicz-Kłosowska, Dorota (Doświadczanie i wyrażanie włoskości: Aspekty językoznawcze i glottodydaktyczne, 2021)
The subject of the analysis are the lexical exponents of the concept of “civil society” and “social responsibility” taken from the corpus of texts of Italian and Polish social advertising (1972-2017). The term “civil society” generally means the involvement of each person in the construction of propitious living conditions within a given social reality. It is an attitude characterized by the voluntary activity of citizens, in favor of changes for the better in their social environment. It is based on the assumption that each individual has an impact on quality of life at the local and supra-local level. The starting point for considering the concept of “civil society” is an autonomous, tolerant, open unit, ready to act for the good of others. The article aims to verify which linguistic exponents from the pro publico bono advertising form an open definition of the concept taken into consideration, in the last 50 years in Poland and in Italy, in a comparative key.